Revealing The Causes Of Unoptimized Internal Auditor Performance At Higher Educa-tion In The Maluku Region - Dwi Hariyanti; Jaelani La Masidonda (International Journal of Artificial Intelligence Research, 2022)
This study aims to reveal the performance of internal quality auditors who have not been optimal through examining the factors that influence the performance of internal quality auditors at private universities (PT) in the Maluku region. This research is a quantita-tive research, the object of research is at private universities in the Maluku region. Con-ducting research in February 2022-March 2023. The research sample is an internal quality auditor with a total of 43 respondents, with saturated sample criteria. The ana-lytical tool, namely inferential analysis, is used by SPSS through Multiple Regression. The results of the study explained that the cause of the non-optimal performance of in-ternal quality auditors at tertiary institutions in the Maluku Region was the support from university leaders and foundations. Meanwhile, what supports the performance of internal quality auditors that are still running today are the factors of competence, inde-pendence and quality culture owned by internal quality auditors of higher education. In order to optimize the performance effectiveness of internal quality auditors in tertiary institutions, support from the tertiary top management is urgently needed.